Ideologi Patriotisme dalam "Battle of Surabaya": Representasi dan Relevansinya untuk Pembelajaran Bahasa Indonesia - Hila Lisa Riskiawati; Babul Bahrudin; Ahmad Ilzamul Hikam (Hasta Wiyata, 2025)
This study aims to analyze the representation of the ideology of patriotism in the animated film Battle Of Surabaya is depicted and analyze the relevance of the animated film Battle Of Surabaya in learning Indonesian in high school. This research uses a qualitative approach with a descriptive research type Likewise, the analytical tool in this study uses Jhon Fiske's semiotics. The research instrument is the researcher himself. The data and data sources in this study are research informants, observed phenomena, and documentation. Data collection techniques are observation, interviews, documentation, and notes. Data analysis techniques in this study are data collection, data coding, data presentation, and drawing conclusions. checking the validity of the data used is triangulation of sources, methods, and theories. The results that have been found are four attitudes of patriotism, courage, three are willing to sacrifice, and one is love for the nation and state. In addition, this study also found the results of observations, interviews, documentation, and notes about the relevance of the animated film Battle Of Surabaya in learning Indonesian at SMA Negeri 1 Maron. The relevance of this animated film from the explanation of the teacher and several students of class XI D can be used as effective teaching material and learning media for Indonesian, especially drama text material because this film can make it easier for students to understand the material.